The relationship between Malaysia human resource management and foreign employee retention - Lee, Jenn Yin (2019)
The effectiveness of Malaysia human resource management would improve the tendency of foreign employee retention in the company. Although the personnel management related issues are always critical and difficult to predict, Malaysia company starting to place great emphasis on the retention of foreign employee. This can be view on the degree of importance that company place on human resource practices including recruitment and selection, training and development, performance appraisal, and compensation and benefit. A better understanding on the linkage of these human resource practices which will benefit the company as it is useful in determining the influential on foreign employee retention. This research also contributes directions for the company and future researchers by providing reliable recommendations observed during the process of this research.